SUPREMACY OF LAW IN THE SETTLEMENT OF BANKRUPT DEBTORS’ ASSETS INVOLVED IN CRIMINAL OFFENSES: AN ANALYSIS OF THE CONFLICT BETWEEN GENERAL BANKRUPTCY SEIZURE AND CRIMINAL SEIZURE - Aman, Chairul (Hukum Responsif, 2026)
This study examines the normative and practical conflict between general bankruptcy seizure (sita umum) under Article 21 of the Indonesian Bankruptcy Law and criminal seizure (sita pidana) conducted within criminal proceedings. Using statutory, conceptual, and comparative legal approaches, the research analyzes how overlapping authority between bankruptcy trustees (curators) and criminal law enforcement institutions-investigators, prosecutors, and the Corruption Eradication Commission (KPK)-creates legal uncertainty in the administration of debtor assets. The study finds that jurisprudential practices in Indonesia frequently prioritize criminal seizure, thereby undermining the bankruptcy principle of pari passu pro rata parte and weakening creditor protection. Through comparative insights, particularly from Malaysia’s insolvency framework, this research proposes a legal harmonization model that emphasizes coordination mechanisms between bankruptcy administration and criminal asset recovery regimes to uphold legal certainty, fairness to creditors, and the supremacy of law. In Indonesia, problems emerge when a debtor is declared insolvent while concurrently undergoing criminal prosecution. This study analyzes the legal conflict between sita umum (general bankruptcy seizure), which guarantees equitable distribution among creditors, and sita pidana (criminal seizure), which safeguards assets for evidentiary purposes, confiscation, or reparation. This study employs a normative legal research methodology, incorporating statutory review, jurisprudence, and comparative analysis, to assess the Bankruptcy Law (Law No. 37/2004), the Criminal Procedure Code (KUHAP), and supplementary legislation, including the Anti-Money Laundering Law. Research indicates that Indonesian jurisprudence emphasizes criminal seizure, particularly in situations of corruption and fraud, frequently undermining creditor protection due to a lack of standardized regulations. A comparative analysis of Malaysia reveals a better integrated structure that protects creditors' rights while considering criminal justice objectives. Findings show that Indonesian jurisprudence prioritizes criminal seizure, especially in corruption and fraud cases, often weakening creditor protection due to the absence of harmonized regulations. A comparative review of Malaysia demonstrates a more coordinated framework that safeguards creditors’ rights while accommodating criminal justice interests. The study concludes that harmonization of Indonesian regulations, stronger coordination between curators and law enforcement, and clearer guidelines on overlapping claims are crucial to achieving legal certainty, creditor protection, and enforcement of justice. The institutional conflict between bankruptcy administration and criminal law enforcement has become increasingly visible in cases in which debtor assets are simultaneously subject to both bankruptcy proceedings and criminal investigations. In practice, curators responsible for managing bankruptcy estates often face competing claims from investigators or prosecutors seeking criminal seizure of the same assets. This institutional overlap generates uncertainty regarding which legal regime should prevail. Without clear coordination mechanisms, the enforcement of criminal law may inadvertently undermine the collective creditor protection principle embedded in bankruptcy law.